A guide to microlife - Rainis, Kenneth G (New York Franklin Watts, 1996)
Serves as a guide to be used for the identification of microorganisms and provides information about microlife forms and how they affect other life forms, including human
Hurg
5
Keywords: Microorganisms -- Identification -- Atlases -- Juvenile literature; Microscopy -- Juvenile literature